Health awareness in female doctors - Wagh, Reena V.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2018)
Background: Managing the hectic schedule, female doctors often neglect their own health. In the present study, we evaluated the awareness, attitude and practices of breast, cervical and ovarian malignancies and also hypertension, diabetes, coronary artery disease and osteoporosis in female doctors. Methods: A cross sectional study was conducted among 100 female doctors of M.B.B.S. and higher degrees of various subjects. Selection of female doctors was done randomly. Results: In present study, out of 100 female doctors, 90 (90%) were doing their self breast examination regularly and 31 (31%) had done their mammography. 54 (54%) female doctors had their own pap smear done while 72 (72%) female doctors had their own ultrasound got done. 82 (82%) had their own blood pressure check up, 74 (74%) had their own blood sugar checked, 62 (62%) had got their own lipid profile done while only 44 (44%) female doctors had their ECG done and 48 (48%) had their bone mineral density done. 23 (23%) female doctors were diagnosed as hypertensive, 14 (14%) as diabetes, 4 (4%) as coronary artery disease, 5 (5%) as breast cancer, 2 (2%) as ovarian cancer, 18 (18%) as thyroid disease while 15 (15%) were detected as having osteopenia. Conclusions: In spite of knowing about all diseases, their complications, screening methods and preventive care, practice of applying screening or preventive methods to themselves is not universal in doctors.